Aplikasi Android Lampu Led Berbasis Arduino - Fitria Rahmadayanti (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2016)
Technology development and application of tools, machines, materials and processes that help humans solve the problem. With the development of this technology to encourage people to bring new ideas to simplify all activities of daily living. Controlling the house lights for example. To control house lights manually can take a lot of time in operation. With advances in technology can be built a lighting control system using android smartphone. Type mobile phone (cell phone) smartphone category are much in demand by the public for kecanggihanya. Most smartphones have operating systems based on Android. Android is an operating system for Linux-based mobile devices that includes an operating system, middleware and applications. System development method used is prototype with stages Collecting and analyzing needs, build prototyping, evaluation protoptyping, build systems, test systems, evaluation systems, use the system. To create the application using APP MIT Inventor with type parallel circuit connected with bluetooth and Relay to regulate the flow of electrical current is greater as needed by using a control system with a small electrical current into the device arduino Uno type.